Results 1 to 5 of 5

Math Help - Multiplying power series - Maclaurin series

  1. #1
    Newbie
    Joined
    Oct 2008
    Posts
    6

    Multiplying power series - Maclaurin series

    Hi, I've run into some trouble trying to answer this power series question that asks:

    Use multiplication or division of power series to find the first three nonzero terms in the Maclaurin series for the given function.

    e^{7x}ln(1-x/5)

    This is my work so far (all sums are n=0 to infinity):
    e^x = \sum \frac{x^n}{n!}

    e^{7x} = \sum \frac{7^nx^n}{n!}

    and
    <br />
ln(1+x) = \sum (-1)^{n-1}\frac{x^n}{n}

    ln(1-x/5) = \sum (-1)^{n-1}(-1)^n\frac{5^{-n}x^n}{n}
    ln(1-x/5) = \sum (-1)^{2n-1}\frac{x^n}{n5^n}

    To find the first 3 non-zero terms, I think I'm supposed to do something like the following:

    n=3 \longrightarrow a_0b_3+a_1b_2+a_2b_1+a_3b_0
    n=2 \longrightarrow a_0b_2+a_1b_1+a_2b_0
    n=1 \longrightarrow a_0b_1+a_1b_0
    n=0 \longrightarrow a_0+b_0

    What I got from doing that was:
    ( (-1)^{2n-1} becomes -1 for all n)

    n=3
    -\frac{(7x)^0}{0!}*\frac{x^3}{3(5^3)}-\frac{(7x)^1}{1!}*\frac{x^2}{2(5^2)}-\frac{(7x)^2}{2!}*\frac{x^1}{1(5^1)}-\frac{(7x)^3}{3!}*\frac{x^0}{0(5^0)}
    = -\frac{x^3}{375}-\frac{7x^3}{50}-\frac{49x^3}{10}-\frac{343x^3}{0}
    = -\frac{3781x^3}{375}-\frac{343x^3}{0}

    n=2
    -\frac{(7x)^0}{0!}*\frac{x^2}{2(5^2)}-\frac{(7x)^1}{1!}*\frac{x^1}{1(5^1)}-\frac{(7x)^2}{2!}*\frac{x^0}{0(5^0)}
    = -\frac{x^2}{50}-\frac{7x^2}{5}-\frac{49x^2}{0}
    = -\frac{71x^2}{50}-\frac{49x^2}{0}

    n=1
    -\frac{(7x)^0}{0!}*\frac{x^1}{1(5^1)}-\frac{(7x)^1}{1!}*\frac{x^0}{0(5^0)}
    = -\frac{x}{5}-\frac{7x}{0}

    n=0
    -\frac{(7x)^0}{0!}-\frac{x^0}{0(5^0)}
    -1-\frac{1}{0}

    How do I get my 3 terms from the above? I have a lot of fractions where I'm dividing by 0.
    Edit: I just realized that I changed e^{7x} into a power series, would the Maclaurin series for that function be the same?
    Last edited by triggy; March 7th 2009 at 06:04 AM. Reason: Fixing grammar
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Moo
    Moo is offline
    A Cute Angle Moo's Avatar
    Joined
    Mar 2008
    From
    P(I'm here)=1/3, P(I'm there)=t+1/3
    Posts
    5,618
    Thanks
    6
    Hello,

    I haven't checked your formulae, it looks long


    However, note that the power series of the exponential starts at n=0, and the power series of the logarithm stars at n=1.
    This should solve the problem of dividing by 0.

    The MacLaurin series is a power series. The expansion of a function into a series is unique. So expanding a function as a power series is equivalent to getting the MacLaurin series. (I don't know if I'm clear here ? :s)



    To simplify calculations, you can use the Cauchy product for series. But again, be careful that the series should start at the same point
    Last edited by Moo; March 8th 2009 at 12:51 PM. Reason: removing a useless parenthesis
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Newbie
    Joined
    Oct 2008
    Posts
    6
    Alright, so if I changed the index for the logarithmic series to start at 1, the following:

    n=3
    n=2
    n=1
    n=0

    ..would change to:

    n=3 \longrightarrow a_0b_3 + a_1b_2 + a_1b_1
    n=2 \longrightarrow a_0b_2 + a_1b_1
    n=1 \longrightarrow a_0b_1

    Would that be correct?
    Follow Math Help Forum on Facebook and Google+

  4. #4
    Newbie
    Joined
    Oct 2008
    Posts
    6
    Actually, forget about the last reply.

    I rechecked my work and fixed the power series for the ln function. I'll show my work for it.

    ln(1+x) = \sum (-1)^{n+1}\frac{x^{n+1}}{n+1}

    ln(1-x/5) = \sum (-1)^{n+1}\frac{(-\frac{x}{5})^{n+1}}{(n+1)}
    ln(1-x/5) = \sum (-1)^{n+1}(-1)^{n+1}\frac{x^{n+1}}{(n+1)5^{n+1}}
    ln(1-x/5) = \sum (-1)^{2n+2}\frac{x^{n+1}}{(n+1)5^{n+1}}
    ln(1-x/5) = \sum \frac{x^{n+1}}{(n+1)5^{n+1}}


    a_n = \sum \frac{(7x)^n}{n!}
    b_n = \sum \frac{x^{n+1}}{(n+1)5^{n+1}}

    With the n=3 \longrightarrow a_0b_3 + a_1b_2 + ... etc. and same for n=2, n=1, n=0

    I got:
    n=0 \longrightarrow 1+\frac{x}{5}
    n=1 \longrightarrow \frac{71x^2}{50}
    n=2 \longrightarrow \frac{3782x^3}{750}
    n=3 \longrightarrow \frac{89568x^4}{7500}

    So are the first 3 non-zero terms of the series: 1, \frac{x}{5}, and \frac{71x^2}{50}?
    Follow Math Help Forum on Facebook and Google+

  5. #5
    Moo
    Moo is offline
    A Cute Angle Moo's Avatar
    Joined
    Mar 2008
    From
    P(I'm here)=1/3, P(I'm there)=t+1/3
    Posts
    5,618
    Thanks
    6
    There is a little problem in the Taylor series for the logarithm !

    The formula is \ln(1+x)=\sum_{n=1}^\infty (-1)^{n-1} \frac{x^n}{n}
    which is \sum_{n=0}^\infty (-1)^{\color{red}n} \frac{x^{n+1}}{n+1}

    so \ln(1-x/5)={\color{red}-} \sum_{n=0}^\infty \frac{\left(\tfrac x5\right)^{n+1}}{n+1}


    this last modification should give you the correct answers


    Edit : there is another problem, c_0=a_0b_0=-\frac x5. There is no 1
    Last edited by Moo; March 8th 2009 at 12:21 AM.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Maclaurin/Taylor/Power Series clarification
    Posted in the Calculus Forum
    Replies: 8
    Last Post: September 10th 2010, 05:42 AM
  2. Replies: 0
    Last Post: January 26th 2010, 08:06 AM
  3. Question - Power/taylor/MacLaurin series
    Posted in the Calculus Forum
    Replies: 1
    Last Post: November 9th 2009, 10:25 PM
  4. Multiplying/Dividing Power Series
    Posted in the Calculus Forum
    Replies: 2
    Last Post: April 16th 2009, 05:33 PM
  5. Calculus: Multiplying two power series
    Posted in the Calculus Forum
    Replies: 2
    Last Post: April 5th 2007, 09:13 AM

Search Tags


/mathhelpforum @mathhelpforum